2012
DOI: 10.1152/jn.00535.2011
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific serotonergic facilitation of IPSC in layer 2/3 pyramidal neurons of the visual cortex

Abstract: Jang HJ, Cho KH, Park SW, Kim MJ, Yoon SH, Rhie DJ. Layer-specific serotonergic facilitation of IPSC in layer 2/3 pyramidal neurons of the visual cortex. J Neurophysiol 107: 407-416, 2012. First published October 19, 2011 doi:10.1152/jn.00535.2011 inhibits the induction of longterm synaptic plasticity in layer 2/3 of the visual cortex at the end of its critical period in rats. However, the cellular and molecular mechanisms remain unclear. Since inhibitory influence is crucial in the induction of synaptic plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
1
27
0
1
Order By: Relevance
“…1) and in our previous study (Jang et al, 2012). Bicuculline at the concentration of 300 nM could reverse the $20% increase in IPSCs by 5-HT (data not shown).…”
Section: Functional Roles Of the Modulation Of Phasic And Tonic Inhibsupporting
confidence: 50%
See 4 more Smart Citations
“…1) and in our previous study (Jang et al, 2012). Bicuculline at the concentration of 300 nM could reverse the $20% increase in IPSCs by 5-HT (data not shown).…”
Section: Functional Roles Of the Modulation Of Phasic And Tonic Inhibsupporting
confidence: 50%
“…In our previous study on 5-HT regulation of IPSC (Jang et al, 2012), we noticed that 5-HT also affects holding currents as well as IPSCs. This suggested that 5-HT might also regulate tonic GABA A R currents.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations